1999
DOI: 10.1176/ajp.156.6.869
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Minimal Effective Dose of Risperidone Based on PET-Measured D2 and 5-HT2A Receptor Occupancy in Schizophrenic Patients

Abstract: Treatment with risperidone, 6 mg/day, is likely to induce unnecessarily high D2 receptor occupancy, with a consequent risk of extrapyramidal side effects. High 5-HT2A receptor occupancy did not prevent extrapyramidal side effects completely. The authors previously suggested an optimal interval for D2 receptor occupancy of 70%-80%. To achieve this, resperidone, 4 mg/day, should be a suitable initial dose for antipsychotic effect with a minimal risk of extrapyramidal side effects in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(143 citation statements)
references
References 29 publications
13
127
0
3
Order By: Relevance
“…As reported by Schotte et al (1996), these agents, including clozapine, risperidone, 9-hydroxyrisperidone (paliperidone), olanzapine, pipamperone, quetiapine, sertindole, ziprasidone, and zotepine, also have higher occupancy in the rat cortex and striatum of 5-HT 2A than D 2 receptors, respectively, at all but the highest doses studied. PET studies are also consistent with the view that at clinically relevant doses, those agents, which are direct acting antagonists of D 2 receptors, have higher occupancy of D 2 than 5-HT 2A receptors (Goyer et al, 1996;Nyberg et al, 1999;Gefvert et al, 2001;Kessler et al, 2005). Aripiprazole, a partial D 2 receptor agonist, has a higher D 2 than 5-HT 2A receptor occupancy at clinical doses, but, nevertheless, has a weak functional effect to inhibit D 2 receptor stimulation (Mamo et al, 2007).…”
Section: Da Effluxsupporting
confidence: 69%
“…As reported by Schotte et al (1996), these agents, including clozapine, risperidone, 9-hydroxyrisperidone (paliperidone), olanzapine, pipamperone, quetiapine, sertindole, ziprasidone, and zotepine, also have higher occupancy in the rat cortex and striatum of 5-HT 2A than D 2 receptors, respectively, at all but the highest doses studied. PET studies are also consistent with the view that at clinically relevant doses, those agents, which are direct acting antagonists of D 2 receptors, have higher occupancy of D 2 than 5-HT 2A receptors (Goyer et al, 1996;Nyberg et al, 1999;Gefvert et al, 2001;Kessler et al, 2005). Aripiprazole, a partial D 2 receptor agonist, has a higher D 2 than 5-HT 2A receptor occupancy at clinical doses, but, nevertheless, has a weak functional effect to inhibit D 2 receptor stimulation (Mamo et al, 2007).…”
Section: Da Effluxsupporting
confidence: 69%
“…Third, our patients were scheduled to receive a target dose of 4 mg/day of risperidone rather than a standard dose of 6 mg/day. A low risk of EPS was observed among these subjects, as was suggested by several other studies (Nyberg et al, 1999;Williams, 2001). Consequently, we were able to maintain a uniform dosage schedule for most patients.…”
Section: Discussionsupporting
confidence: 83%
“…In line with the in vivo data (see above), most of the atypical drugs display higher 5-HT 2A than D 2 occupancy rates when dual-tracer approaches are used (Kapur et al, 1998;Nyberg et al, 1999;Gefvert et al, 2001;Mamo et al, 2004). But although it was suggested that the predominant 5-HT 2A receptor antagonism of atypical drugs protects against EPS (Meltzer, 1999), even atypical substances such as olanzapine or risperidone cause EPS when given in higher doses that lead to D 2 receptor occupancy of more than 80% (Kapur et al, 1998;Nyberg et al, 1999).…”
Section: Antipsychotic Drug Action and Serotonin Receptor Occupancymentioning
confidence: 61%
“…But although it was suggested that the predominant 5-HT 2A receptor antagonism of atypical drugs protects against EPS (Meltzer, 1999), even atypical substances such as olanzapine or risperidone cause EPS when given in higher doses that lead to D 2 receptor occupancy of more than 80% (Kapur et al, 1998;Nyberg et al, 1999). receptors (-2-44%) at doses between 10 to 30 mg in schizophrenia patients.…”
Section: Antipsychotic Drug Action and Serotonin Receptor Occupancymentioning
confidence: 99%